Lifeblood - Becker, Tom (New York Orchard Books, 2008)
As Jonathan searches London's Darkside for the same murderer that his mother was seeking when she disappeared twelve years earlier, it becomes clear that it is Jonathan who is being hunted
Hurg
5
Keywords: Horror stories; Supernatural -- Fiction; England -- Fiction